Cyberbullying, Mental Health, and Violence in Adolescents and Associations With Sex and Race: Data From the 2015 Youth Risk Behavior Survey - Mohammed Alhajji MPH; Sarah Bass PhD, MPH; Ting Dai PhD (SAGE Publishing, 2019)
Background . Cyberbullying is a serious issue among adolescents, but little is known about how demographics are associated with mental health conditions and violent behaviors. The present study examined the association of cyberbullying victimization with mental health conditions and violent behaviors among adolescents, specifically examining potential differences by sex and race. Methods . National data obtained from a representative sample of 9th to 12th grade students (N = 15 465) in the United States were examined using bivariate and logistic regression analysis. Results . More than 15% of students reported cyberbullying victimization. Females were twice as likely to report victimization than males, and non-white students were 50% less likely to report cyberbullying victimization. Cyberbullying victimization was significantly more likely in students who reported depressive symptoms, suicidal ideation, suicide planning, carrying a weapon, and engaging in a physical fight. These associations were more pronounced in males. Conclusions . Our findings show that female and white adolescents are at increased risk of being cyberbullied. However, negative mental health outcomes and violent behaviors are more pronounced in males, indicating potential negative effects of being a cyberbullying victim based on sex. We envisage the best way to combat cyberbullying is to develop programs that are sensitive to potential demographic differences to empower students based on individual risks.